Ku "jedności natchnień i znaczeń". Nad rękopisem "Wigilii wielkanocnej 1966" Karola Wojtyły = Towards "unity of inspirations and meanings". On the manuscript "Easter Vigil 1966" by Karol Wojtyla - Kozłowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the original of the Karol Wojtyła`s poem "Wigilia wielkanocna 1966" ("Easter Vigil 1966"), namely the manuscript stored in the Cracow Curia Archive. The main goal of the paper is to show basic directions of the Wojtyła`s work on the text of this poem.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; polish poetry; manuscript; poezja polska - 20 w.; rękopis